SEARCH EFFECT CHANGE THE OBJECTIVE FUNCTIONCOEFFICIENTS TO THE OPTIMAL SOLUTION WITH PRACTICALAPPLICATION(USE THE PARAMETRIC PROGRAMMING) - Ibrahim, Sameerh (Iraqi Journal of Science, 2024)
The parametric programming considered as type of sensitivity analysis. Thispaper is concern on the study the effect of the variations objective functioncoefficients on the optimal solution. Of the parameter value (-5 ≤ θ ≤ 50) is taken theresult, of the objective function equal zero and the decision variables are non basic,when the parameter (θ = -5).The objective function have value maximum when theparameter (θ= 50) and the decision variables are become basic. Whenever theparameter value increase, the objective function value increase too.